An extended reconstruction of human gut microbiota metabolism of dietary compounds - Telmo Blasco; Sergio Pérez-Burillo; Francesco Balzerani; Daniel Hinojosa-Nogueira; Alberto Lerma-Aguilera; Silvia Pastoriza; Xabier Cendoya; Ángel Rubio; María José Gosalbes; Nuria Jiménez‐Hernández; M. Pilar Francino; Iñigo Apaolaza; et al. (2021)
Understanding how diet and gut microbiota interact in the context of human health is a key question in personalized nutrition. Genome-scale metabolic networks and constraint-based modeling approaches are promising to systematically address this complex problem. However, when applied to nutritional questions, a major issue in existing reconstructions is the limited information about compounds in the diet that are metabolized by the gut microbiota. Here, we present AGREDA, an extended reconstruction of diet metabolism in the human gut microbiota. AGREDA adds the degradation pathways of 209 compounds present in the human diet, mainly phenolic compounds, a family of metabolites highly relevant for human health and nutrition. We show that AGREDA outperforms existing reconstructions in predicting diet-specific output metabolites from the gut microbiota. Using 16S rRNA gene sequencing data of faecal samples from Spanish children representing different clinical conditions, we illustrate the potential of AGREDA to establish relevant metabolic interactions between diet and gut microbiota.